Artificial intelligence integration in the drug lifecycle and in regulatory science: policy implications, challenges and opportunities - Oualikene-Gonin, Wahiba; Jaulent, Marie-Christine; Thierry, Jean-Pierre; Oliveira-Martins, Sofia; Belgodère, Laetitia; Maison, Patrick; Ankri, Joël; , The Scientific Advisory Board of ANSM (Frontiers in Pharmacology, 2024)
Artificial intelligence tools promise transformative impacts in drug development.• Regulatory agencies face challenges in integrating AI while ensuring reliability and safety in clinical trial approvals, drug marketing authorizations, and post-market surveillance.• Incorporating these technologies into the existing regulatory framework and agency practices poses notable challenges, particularly in evaluating the data and models employed for these purposes.• Rapid adaptation of regulations and internal processes is essential for agencies to keep pace with innovation, though achieving this requires collective stakeholder collaboration.• This article thus delves into the need for adaptations of regulations throughout the drug development lifecycle, as well as the utilization of AI within internal processes of medicine agencies.